Communication breakdowns during business process change projects – Insights from a sociotechnical case study. Issue 3 (April 2022) - Saxena, Deepak; McDonagh, Joe
Highlights: Communication breakdowns pose challenges during complex projects. Communication is the medium through which change happens. Successful change management requires a multilevel communication approach. Abstract: Despite an acknowledgment of the importance of communication in project management, communication breakdowns still occur with a negative influence on project success. In existing literature, communication is usually reduced to an instrument for ensuring employee buy-in and overcoming user resistance towards the end of the project. The purpose of this study is to examine the communication breakdowns occurring at multiple levels during a business process change project. This study employs a qualitative longitudinal case study design embedded within a sociotechnical systems lens, focussing on the work-system, organisational, and macrosocial levels. Based on the findings of the case study of a new blood labelling system implementation in a national blood bank service, this study empirically illustrates the occurrence of communication breakdowns during a project. The study suggests that the occurrence of these communication breakdowns can be avoided by change communication in relation to the context, process, and content of change respectively at the macrosocial, organisational, and the work-system levels. The study also demonstrates the contextual influence of the health sector, and in so doing, establishes the requirement towards system flexibility to accommodate diverse solutions when planning and executing a project.